Effects of 12 weeks of heavy strength training on muscle strength and performance in elite cross-country skiers - Hallen, J.; Losnegard, T. J.; Mikkelsen, K. L.; Ronnestad, B.; Ure, J.; Kvamme, N. H.; Rud, B.; Jakobsen, V. E.; Hem, E.; Leirstein, S.; Kvamme, B.; Raastad, T. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Cross-country skiing is a typical endurance sport with high reliance on maximal aerobic power. Nevertheless, improvements in performance by increasing muscle strength and power, especially in the upper body, has been reported. Also, anaerobic power is reckoned a determinant for cross-country performance, especially in sprint (Stöggl et al., 2007). From this, strength training should be beneficial for cross-country skiers. However, high volume endurance training may be antagonistic to strength training induced strength gain and may therefore not have any effect on cross-country performance. The present study aims at testing if heavy strength training affects muscle strength and cross-country ski performance in well trained skiers.